Calcium deposition in egg due to substitution of limestone by eggshell flour in feed of laying hens - Kismiati, S.; Yuwanta, T.; Zuprizal, Z.; Supadmo, S.; Atmomarsono, U. (Diponegoro University, 2018)
The aim of this research was to evaluate calcium deposition in egg using eggshell flour as a limestone substitute in feed. Two hundreds laying hen of Isa Brown strain of 25 weeks were used in this study. Treatments were diet with 7.5% limestone as control (T0), 2.5% limestone is substituted with eggshell flour(T1), 5% limestone is substituted with eggshell flour (T2) and limestone is substituted with eggshell flour (T3). A completly randomized design were used to allocated the treatments with 5 replications of each. Each experimental unit consists of 10 laying hens. Parameters measured were egg weight, yolk weight, albumen weight, eggshell weight, calcium of egg (yolk, albumen and eggshell), length, weight and Ca of tibia bone. The results showed that substitution of limestone with eggshell flour had significantly effect (P<0.05) on eggshell weight, Ca deposition on yolk, albumen, and Ca of tibia bone but non significantly effect on egg weight, weight and percentage of yolk, weight and percentage of albumen, percentage and Ca of eggshell, length and weight of tibia bone. In conclusion, calcium deposition in yolk was the highest in the use of 7.5% eggshell flour to substitute limestone but obtained the lowest Ca of bone , while calcium deposition in albumen was the highest in the use of 2.5% eggshell flour.